Pengembangan Modul Fisika Materi Suhu dan Kalor Terintegrasi Ayat Al-Qur’an - Ratih Widya Ningsi; Hasbullah Hasbullah; Muhammad Qaddafi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study addresses the challenge of engaging students in traditional physics education, particularly in Islamic contexts where integrating spirituality is often difficult. It presents a developed physics module for Grade XI students at MAN 1 Selayar that combines Quranic verses with temperature and heat concepts, using the 4D development model (Define-Design-Develop). The module bridges scientific understanding with Islamic values, and its effectiveness was tested with 20 students. Expert validation resulted in a high 0.94 validity score, confirming its scientific accuracy. Student feedback was overwhelmingly positive, with 90% rating the module as "highly practical," and 85% of students achieving mastery (≥70%). This exceeded the 80% effectiveness threshold, reflecting significant learning improvement. Additionally, the module fostered increased student curiosity about the connection between physics and Islam, motivating further exploration of scientific concepts and enhancing their appreciation of how natural phenomena reflect divine creation. Ultimately, this innovative approach demonstrates that physics education can effectively integrate academic and spiritual growth, offering educators a valuable tool to enhance both academic performance and faith-based learning in Islamic science education.